AB0945 Clues to Recognize Fibromyalgia From a Patient Self-Report Multidimensional Health Assessment Questionnaire (MDHAQ) and Physician Rheumetric Checklist. (9th June 2015) - Nikiphorou, E.; Negoescu, A.F.; Castrejon, I.; Pincus, T.
Abstract : Background: Fibromyalgia (FM) is characterized by widespread musculoskeletal pain and a broad range of symptoms. While FM generally is easily recognized, it may pose a diagnostic challenge, particularly in patients with mild inflammatory diseases. Objectives: To assess whether a two-page patient self-report Multidimensional Health Assessment Questionnaire (MDHAQ) and one-page physician RHEUMETRIC checklist can provide strong clues to the presence of FM. Methods: All patients seen in one academic clinical setting complete a two-page MDHAQ in 5-10 minutes in the waiting area, prior to seeing the rheumatologist, in the infrastructure of usual care. The MDHAQ includes physical function (FN) in 10 activities of daily living scored 0-10, three 0-10 visual analog scales (VAS) for pain (PN), patient global estimate (PATGL), and fatigue (FT), a 60-item symptom checklist, and demographic data. Scores were computed for RAPID 3 (0-30, i.e., the sum of three 0-10 scores for FN, PN and PATGL), total number of symptoms (0-60), and fatigue VAS. RHEUMETRIC is a one-page physician checklist with four 0-10 VAS for overall global patient status (DOCGL), and levels of inflammation (reversible signs) (DOCINFL), damage (irreversible signs) (DOCDAM), and "neither" inflammation nor damage (DOCNON) e.g. fibromyalgia. Mean MDHAQ and RHEUMETRIC scores were compared in 4 diagnosis groups: rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), osteoarthritis (OA), fibromyalgia (FM), using MANOVA, adjusted for age, symptom duration and education. Results: Analyses included 205 patients, 50 with RA, 66 with SLE, 57 with OA, and 32 with FM. Mean scores on each of the MDHAQ scales were significantly higher in FM than in other diagnoses (p<0.01) (Table ). DOCGL also was highest in FM, while DOCINF was significantly lower. DOCINF was highest in RA, DOCDAM was highest in OA, and DOCNON was highest in FM (p<0.001) (Table ). Conclusions: A diagnosis of FM is made on the basis of a patient history and physical examination. Simple 2-page patient and physician questionnaires provide standard information from a patient history and physician evaluation, which may include useful clues to the presence of FM. Completion of an MDHAQ by each patient and RHEUMETRIC by rheumatologists at each visit could be of value to recognize FM in busy clinical settings. Disclosure of Interest: None declared